Secure Technique to Achieve Data Privacy and Data Integrity in Cloud Computing - Saxena, Shraddha; Sharma, Manish (International Journal of Computer Sciences and Engineering, 2025)
Cloud services are increasing day by day over the Internet. Using the cloud services both time and money will be saved for user. However, there are some security problems to be solved for users and enterprises for data storing in secure way in the cloud. The real fact is that when users will have not any kind of physical control on outsourced data. Cloud user is concerned about the security and integrity of data stored in the cloud environment as it can be attacked by attacker. The purpose of this research paper using Third Party Auditor an efficient public data auditing technique works for verify the security and integrity of data. Which data is stored in the cloud. The proposed auditing technique makes use of Secure Hash Algorithm (SHA-2) for generating verification meta data and message digest for data integrity authentication and AES algorithm for encryption. Analysis of proposed technique shows provably more secure and TPA takes a constant time to audit files of different sizes.